Energy Efficient Homes: Laundry Area - Hyun-Jeong Lee; Kathleen C. Ruppert; Wendell A. Porter (EDIS)
FCS-3260, a 5-page illustrated fact sheet by Hyun-Jeong Lee, Kathleen C. Ruppert, and Wendell A. Porter, is part of the Energy Efficient Homes series. It discusses how to save energy in the laundry area including where it should be located, how to use current washing machines and dryers more efficiently, how to buy a new appliance. Includes references. Published by the UF Department of Family, Youth and Community Sciences, June 2008.